Sex and Gender in COVID-19 Vaccine Research: Substantial Evidence Gaps Remain - Vassallo, Amy; Shajahan, Sultana; Harris, Katie; Hallam, Laura; Hockham, Carinna; Womersley, Kate; Woodward, Mark; Sheel, Meru (Frontiers in Global Women's Health, 2021)
Since the start of the COVID-19 pandemic there has been a global call for sex/gender-disaggregated data to be made available, which has uncovered important findings about COVID-19 testing, incidence, severity, hospitalisations and deaths. This mini review scopes the evidence base for efficacy, effectiveness and safety of COVID-19 vaccines from both experimental and observational research, and asks whether 1) women and men were equally recruited and represented in vaccine research, 2) the outcomes of studies were presented or analysed by sex and/or gender, and 3) there is evidence of sex and/or gender differences in outcomes. Following a PubMed search, 41 articles were eligible for inclusion, including seven randomised controlled trials (RCTs), eleven cohort studies, eight cross-sectional surveys, eight routine surveillance studies and seven case series. Overall, the RCTs contained equal representation of women and men; however, the observational studies contained a higher percentage of women. Of ten studies with efficacy data, only three (30%) presented sex/gender-disaggregated results. Safety data was included in 35 studies and only 12 (34%) of these presented data by sex/gender. For those that did present disaggregated data, overall, the majority of participants reporting adverse events were women. There is a paucity of reporting and analysis of COVID-19 vaccine data by sex/gender. Research should be designed in a gender-sensitive way to present and, where possible analyse, data by sex/gender to ensure that there is a robust and specific evidence base of efficacy and safety data to assist in building public confidence and promote high vaccine coverage.